2020
DOI: 10.1155/2020/2627471
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography of the Vagus Nerve in the Diagnosis of Parkinson’s Disease

Abstract: Background. It is currently impossible to diagnose Parkinson’s disease (PD) in the premotor phase even though at the time of motor symptom onset the number of already degenerated dopaminergic substantia nigra neurons is considerable. Degeneration of the dorsal nucleus of the vagus nerve (VN) has been reported early in the disease course, and it could lead to impaired function of the VN, resulting in certain nonmotor symptoms of PD. Therefore, we raised a hypothesis that the loss of VN neurons could result in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 17 publications
(28 reference statements)
2
20
0
Order By: Relevance
“…Our findings confirm the findings of two studies which also found no reduction in CSA of the vagus nerve in PD patients [19,20]. We were unable to replicate the reduction in CSA as reported by earlier studies [16][17][18].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Our findings confirm the findings of two studies which also found no reduction in CSA of the vagus nerve in PD patients [19,20]. We were unable to replicate the reduction in CSA as reported by earlier studies [16][17][18].…”
Section: Discussionsupporting
confidence: 67%
“…Moreover, this method potentially identifies persons at risk even before a clinical diagnosis of PD can be confirmed. It is however important to note that two studies using B-mode ultrasound could not confirm that the CSA of the vagus nerve was decreased in PD [19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac sympathetic neurons are particularly vulnerable in PD (28) and may also contribute to slight vagal atrophy. However, if vagal atrophy is mainly caused by sympathetic and parasympathetic (DMV) axonal loss, the reduction in CSA is probably very small and could explain why three studies failed to show vagal atrophy in PD (20)(21)(22). Additionally, the vagus nerve shows frequent branching (up to 29%) (29).…”
Section: Discussionmentioning
confidence: 99%
“…Four studies found significant atrophy of both left and right vagus nerves in patients with PD (16)(17)(18)(19). In contrast, three studies reported no difference between patients with PD and healthy controls (HCs) (20)(21)(22). Thus, whether ultrasound can detect vagal neuronal loss in patients with PD remains unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence that the structural integrity of the vagus nerve, measured using high-resolution ultrasound, may be altered in PD. Some studies have found that both left and right vagus nerves are significantly smaller in patients relative to age-matched controls [45][46][47], while others have shown a comparable size of the vagus nerve between patients and controls [48][49][50][51].…”
Section: Article Highlightsmentioning
confidence: 99%